A framework of integrated model base for decision support system - Fadhilah Ahmad (Fakulti Sains dan Teknologi, 2012)
Considering just a single criterion mathematical model in a Decision Support System (DSS) for a selection process is not enough. It is essential to consider a multitude of criteria model so that the decision taken is fair and efficient.